The Influence of Market Competition, Company Size, and Corporate Governance on Environmental Management Accounting and Environmental Performance - Vidyarto Nugroho; Urbanus Ura Weruin (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the influence of market competition, company size, and corporate governance on environmental performance, with Environmental Management Accounting (EMA) as a mediating variable. Design/methodology/approach – This study uses a quantitative approach involving managers and accounting professionals from manufacturing and industrial companies listed on the Indonesia Stock Exchange. The data were analyzed using SEM-PLS. Findings/Results – The findings show that market competition, company size, corporate governance, and EMA positively affect environmental performance. EMA also mediates the relationship between market competition, company size, corporate governance, and environmental performance. Originality/Value – This study highlights EMA as a strategic mechanism that connects competitive pressure, organizational capacity, and governance practices with improved environmental performance.